2006
DOI: 10.1038/sj.bjc.6603029
|View full text |Cite
|
Sign up to set email alerts
|

A 3-year prospective study of the effects of adjuvant treatments on cognition in women with early stage breast cancer

Abstract: The neuropsychological performance of 85 women with early stage breast cancer scheduled for chemotherapy, 43 women scheduled for endocrine therapy and/or radiotherapy and 49 healthy control subjects was assessed at baseline (T1), postchemotherapy (or 6 months) (T2) and at 18 months (T3). Repeated measures analysis found no significant interactions or main effect of group after controlling for age and intelligence. Using a calculation to examine performance at an individual level, reliable decline on multiple t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
305
10
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 349 publications
(355 citation statements)
references
References 21 publications
18
305
10
13
Order By: Relevance
“…However, it remains unclear whether postoperative chemotherapy has an effect on cognitive function since different results have been found. Adjuvant CMF chemotherapy caused late cognitive impairment [44] and subjects treated with high-dose chemotherapy with cyclophosphamide, thiotepa and carboplatin showed a decline in cognitive performance compared with healthy controls [45]; however, it has also been found that postoperative chemotherapy had almost no effect on cognitive function [46]. The tendency seems to be that subjective ratings of memory and concentration decrease after treatment with chemotherapy, and that breast cancer patients treated with chemotherapy also seem to be more likely than controls to perceive themselves as impaired [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether postoperative chemotherapy has an effect on cognitive function since different results have been found. Adjuvant CMF chemotherapy caused late cognitive impairment [44] and subjects treated with high-dose chemotherapy with cyclophosphamide, thiotepa and carboplatin showed a decline in cognitive performance compared with healthy controls [45]; however, it has also been found that postoperative chemotherapy had almost no effect on cognitive function [46]. The tendency seems to be that subjective ratings of memory and concentration decrease after treatment with chemotherapy, and that breast cancer patients treated with chemotherapy also seem to be more likely than controls to perceive themselves as impaired [47].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in accordance with the findings of virtually all studies that have reported on the relations between cognitive performance and cognitive complaints. 3,5,7,18,44 Neither chemotherapy-induced menopause nor concomitant darbepoetin a administration had a significant influence on cognitive change.…”
Section: Discussionmentioning
confidence: 99%
“…The results were mixed: Poorer performances were reported among patients who received chemotherapy, 2,3,5,7 although others reported no differences 16,17 ; the latter findings also were supported by a meta-analysis. 21 Two longitudinal studies that provided evidence of chemotherapy effects on cognitive function were limited by their rather small sample sizes (Wefel et 18 did not identify any significant differences in cognitive changes between chemotherapy patients, nonchemotherapy patients, and healthy control individuals. The patients were heterogeneous with regard to the chemotherapy regimens administered, with most patients having received only relatively low-dose combined 5-fluorouracil, epirubicin, and cyclophosphamide treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-El rendimiento objetivo en las pruebas no se relacionó con otras variables como malestar psicológico, calidad de vida y fatiga (22) .…”
Section: Estudios Longitudinalesunclassified